A new species of phytotelm breeding frog (Anura: Rhacophoridae) from the Central Highlands of Vietnam - Rowley, Jodi J. L.; Le, Duong Thi Thuy; Hoang, Huy Duc; Cao, Trung Tien; Dau, Vinh Quang (Zootaxa, 2020)
We describe a new species of phytotelm-breeding rhacophorid frog from central Vietnam. Gracixalus trieng sp. nov. is distinguished from all congeners by a combination of (1) body size medium (37.2–41.4 mm in five adult males), (2) snout rounded in dorsal and lateral views, (3) dorsal surface brown or yellowish with a darker brown interorbital crossbar and inverse-Y shape on the back, (4) throat and chest yellow or yellowish brown with pinkish mottling and belly and ventral surfaces of limbs including hands and feet pinkish, (5) tympanum and supratympanic fold distinct, (6) iris pale gold with darker gold radiating out from anterior and posterior edges of pupil, (7) majority of dorsal body and limb surfaces smooth in adults, with some individuals having sparsely distributed low, irregular tubercles, (8) nuptial pads on fingers I and II in adult males, and (9) eggs deposited as a tightly spaced array of non-pendent eggs on the wall of a phytotelmon. The species occurs in syntopy with G. lumarius. At present, Gracixalus trieng sp. nov. is known only from montane bamboo and evergreen forest (>1700 m) on Mount Ngoc Linh and adjacent peaks; and it is likely to be restricted to high-elevation forest with an estimated geographical distribution of <1000 km2.